2018
DOI: 10.1002/adhm.201701130
|View full text |Cite
|
Sign up to set email alerts
|

Glioma‐Targeted Delivery of a Theranostic Liposome Integrated with Quantum Dots, Superparamagnetic Iron Oxide, and Cilengitide for Dual‐Imaging Guiding Cancer Surgery

Abstract: Herein, a theranostic liposome (QSC-Lip) integrated with superparamagnetic iron oxide nanoparticles (SPIONs) and quantum dots (QDs) and cilengitide (CGT) into one platform is constructed to target glioma under magnetic targeting (MT) for guiding surgical resection of glioma. Transmission electron microscopy and X-ray photoelectron spectroscopy confirm the complete coencapsulation of SPIONs and QDs in liposome. Besides, CGT is also effectively encapsulated into the liposome with an encapsulation efficiency of ∼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 43 publications
0
45
0
Order By: Relevance
“…Xu et al () (X. Wang et al, ) designed a theranostic liposome loaded with cilengitide, a cyclic Arg‐Gly‐Asp peptide with potential anticancer activity, combined SPIONs and QDs into a single platform for magnetic targeting of glioma targeting. In vivo, following magnetic field exposure, the nanoplatform was able to accumulate at tumor sites and inhibit tumor growth.…”
Section: Quantum Dotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al () (X. Wang et al, ) designed a theranostic liposome loaded with cilengitide, a cyclic Arg‐Gly‐Asp peptide with potential anticancer activity, combined SPIONs and QDs into a single platform for magnetic targeting of glioma targeting. In vivo, following magnetic field exposure, the nanoplatform was able to accumulate at tumor sites and inhibit tumor growth.…”
Section: Quantum Dotsmentioning
confidence: 99%
“…They can be functionalized and hybridized with different moieties for tumortargeted real-time imaging in the diagnosis and surgical resection of glioma (Zayed, AbdElhamid, Freag, & Elzoghby, 2019). Xu et al (2018) (X. Wang et al, 2012) designed a theranostic liposome loaded with cilengitide, a cyclic Arg-Gly-Asp peptide with potential anticancer activity, combined SPIONs and QDs into a single platform for magnetic targeting of glioma targeting.…”
Section: Quantum Dotsmentioning
confidence: 99%
“…Different from INOPs in the core, INOPs were produced in the hydrophobic region of phospholipid bilayer with quantum dots (QDs), a new optical imaging method for molecular tracing and biomedical diagnostics, and cilengitide (CGT), inhibiting overexpress of integrin receptors. Using ultrasound-targeted microbubble destruction for delivery, the median survival of glioma rat was significantly extended to 59.6d compared with the control’s (20d) [ 139 ].…”
Section: Application Of Different Coating Of Inops In Cerebral Thementioning
confidence: 99%
“…Cilengitide (an antiangiogenic drug) was encapsulated in the core using a film rehydration method. QDs (CdSe/ZnS) and SPIONs were loaded into liposomal bilayers ( Figure ) . The results showed that the designed dual imaging particles not only provided a negative‐contrast enhancement effect on the glioma through magnetic resonance imaging but also produced tumor emitting fluorescence under magnetic targeting.…”
Section: Hybrid Vesicular Delivery Systemsmentioning
confidence: 99%